ANALISIS HUBUNGAN KESIAPAN BELAJAR SECARA DARING DI ERA PANDEMI COVID-19 TERHADAP HASIL BELAJAR STATISTIKA - Fitry Wahyuni; Muhammad Daut Siagian (Mahesa Research Center, 2020)
This study was motivated by the transformation of the learning process from face-to-face to online learning due to the Covid-19 pandemic. This study aims to analyze students' online learning readiness in the Covid-19 pandemic era regarding statistics learning outcomes. This research is a quantitative descriptive study using a regression research design. Data collection was carried out by providing online learning readiness questionnaires and statistical material tests to students. Based on the results of data analysis, it was found that there was a relationship between online learning readiness and student learning outcomes statistics, with the acquisition price of Fcount = 4.195 and a significance value of 0.048 <0.05, and 46.1% of student statistics learning outcomes were influenced by learning readiness and the rest was influenced by external factors. student learning readiness. Based on these results, it is concluded that online learning readiness affects student learning outcomes statistics, where the large influence of learning readiness is 46.1%. Therefore, so that lecturers and students can maximize factors outside of learning readiness so that the achievements and objectives of the statistics course can be maximally achieved even though learning is carried out online.